3D parametric design and CNC manufacturing of custom solid wood electric guitars using CAD/CAM technology. Issue 2 (4th March 2019) - Krimpenis, A. A.; Chrysikos, M.
ABSTRACT: This study proposes a systematic approach for modelling and three-axis CNC milling of solid wood parts used in stringed electric musical instruments, mainly in electric guitars and basses, through CAD/CAM technology. Design and manufacturing philosophy undertakes particular characteristics of tonal woods, so as to produce high-quality resonant musical instrument parts with high accuracy. To do so, it is crucial to identify design features and to apply the appropriate machining strategies and parameter values based on obtained knowledge, as these have a great impact on both the acoustic characteristics of the parts and on the total appearance of the instrument, thus making it more appealing in a competitive market. Customization of musical instruments is well received among professional musicians who wish to stand out during their performance, as well as to own an instrument of uniquely original shape and sonic properties. Keeping custom instruments cost reasonable is a challenge, unless the overall production is systematic and modular. The proposed approach was developed and tested on a custom solid electric guitar, which was then finished and assembled with off-the-shelf components to form a great looking and sounding electric guitar.